2021
DOI: 10.3389/fpsyt.2021.685451
|View full text |Cite
|
Sign up to set email alerts
|

Mild Cognitive Decline Is a Risk Factor for Scam Vulnerability in Older Adults

Abstract: Research on elderly financial exploitation has mostly focused on financial abuse that occurs in families and other types of trusted relationships. As such, little is known about financial frauds and scams perpetrated by strangers. Financial fraud and scam prevention activities for older adults must be promoted, for which the correlation between the psychological, social, and cognitive characteristics of their vulnerability needs to be determined. The present study aimed to determine whether cognitive decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…For example, male respondents in this study may claim to have a lower level of fear than they actually experience in order to present a strong and tough image in front of others. This speculation is supported by a previous study in which men were found to be more vulnerable to fraud but less likely to report actual victimization [38]. Lastly, no specific attention being given to digital fraud seems to be a limitation in this study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For example, male respondents in this study may claim to have a lower level of fear than they actually experience in order to present a strong and tough image in front of others. This speculation is supported by a previous study in which men were found to be more vulnerable to fraud but less likely to report actual victimization [38]. Lastly, no specific attention being given to digital fraud seems to be a limitation in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, the examination of the linear and non-linear correlations between fraud victimization, vulnerability, fear, and cognitive functioning and psychological characteristics warrants future research. Last, we share the view from the literature [38,39] that the victimization of older adults with significant cognitive impairment is typically under-reported due to their deficit in recognizing and understanding what a scam attempt is.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In this study, we examined the relevance of fraud vulnerability as a psychosocial characteristic associated with fraud victimisation. Scales measuring fraud vulnerability include a scale on telemarketing fraud ( James et al, 2014 ), a scale using scenarios of fraudulent situations ( Zhang et al, 2017 ), and a scale on behavioural, cognitive, and emotional characteristics found in fraud victims ( Ueno et al, 2021 ). James et al (2014) developed a five-item, seven-point telemarketing fraud vulnerability scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study is to clarify the psychosocial characteristics, including fraud vulnerability, of elderly victims of special fraud and older adults who have never experienced fraud, to promote the prevention of such fraud. To clarify fraud vulnerability with fraud victimisation, we used the Scam Vulnerability Scale ( Ueno et al, 2021 ) to compare the scores of each item between the elderly victims of fraud and older adults who have never experienced fraud.…”
Section: Introductionmentioning
confidence: 99%